THE INFLUENCE OF LOCAL CULTURE LEARNINGON STUDENT LEARNING OUTCOMES OF RABIADJALA INPRES ELEMENTARY SCHOOL ARU ISLANDS REGENCY, MALUKU - Ayatullah Muhammadin Al Fath (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
Local culture has an important role in learning. Learning by associating culture with subject matter can make it easier for students to learn. Learning will become more meaningful and easy for students to understand, when the subject matter taught is in accordance with the environment and local culture of students. The purpose of this study was to see the influence of local culture on student learning outcomes at SD Inpres Rabiadjala Dobo City. The results showed that at meeting-1, meeting-2, and meeting-3, there were significant differences in values between the Aru-Javanese, Aru-Bugis, Javanese-Aru, and Bugis-Aru cultures because Sig 0.001 and 0.012 ≤ 0.05. While the Javanese-Bugis and Bugis-Javanese cultures have a value of Sig 1.000 ≥ 0.05, so it can be concluded that there is no significant influence between the Javanese-Bugis and Bugis-Javanese cultures, because the value of Sig ≥ 0.05.